Facile synthesis of the porous FeCo@nitrogen-doped carbon nanosheets as bifunctional oxygen electrocatalysts. (1st March 2020) - Liu, Tingting; Cai, Sheng; Gao, Zhihui; Liu, Shuming; Li, Huani; Chen, Lijuan; Li, Mian; Guo, Hong
Abstract: This work reports the synthesis of novel cross-linked and functional porous carbon nanosheets (CNSs). The polyvinylpyrrolidone/transition metal acetates/N–N-dimethylformamide precursors are first woven into networks by electrospinning. The resultant precursor networks are transformed into the three-dimensional (3D) hierarchically porous material consisting of cross-linked and meso/macroporous CNSs ( i.e., FeCo@NCNS) after pyrolysis. Characterization results prove that abundant ultrafine FeCo@NC units, N–C bonds, metal-nitrogen doped carbon (M-N-C) species and oxygen-containing functional groups disperse along the surfaces of the FeCo@NCNS, which act as electrocatalytic active sites for Oxygen reduction reaction (ORR) and Oxygen evolution reaction (OER). Due to the synergistic effect of the hierarchically porous structures and high-density active sites, the optimal FeCo@NCNS exhibits more positive onset potential (0.98 V relative to a reversible hydrogen electrode ( vs. RHE)) and half-wave potential (0.827 V vs. RHE) than Pt/C (0.97 V vs. RHE and 0.819 vs. RHE) for ORR. Meanwhile, the OER potential at 10 mA cm −2 of the FeCo@NCNS (1.597 V vs. RHE) is more negative than RuO2 (1.631). Furthermore, the oxygen electrode activity (Δ E = E 10, OER - E 1/2, ORR ) of the FeCo@NCNS is as low as 0.772 V, which surpasses the state-of-the-art Pt/C(ORR)-RuO2 (OER) catalyst combination (Δ E = 0.812 V). Experimental results prove that the FeCo@NCNS is among the best non-precious metal based bifunctional electrocatalyst for ORR and OER. Graphical abstract: Under the assistance of static electricity, after optimizing the dosages of metal salt in precursors, a novel three-dimensional hierarchically meso/macroporous hybrid architecture consist of cross-linked, functionalized and porous carbon nanoshewets was successfully designed and synthesized as bi-functional catalyst toward ORR-OER. Image 1 Highlights: Novel 3D hybrid composite stacked by 2D porous and functional FeCo@NCNS. Abundant ultra-fine FeCo@NC units, and metal-N-C (M-N-C) active sites for OER/ORR catalysis. Metal contents controlled structures variation of carbonaceous hybrid composites. Lower (Δ E = E 10, OER - E 1/2, ORR ) of FeCo@NCNS than Pt/C–RuO2 group (0.772 V versus 0.812 V). Superior ORR/OER catalysis stability of 3D hierarchically porous FeCo@NCNS.